The biological effect of three thymosin fraction 5 polypeptides in the murine mixed lymphocyte reaction. - Baxevanis, C N (1985)
The biological effects of three thymosin fraction 5 polypeptides, designated as beta 10, beta 4, and alpha 1 were tested in the MLR of mouse splenocytes, lymph node cells and thymocytes against syngeneic or allogeneic stimulators. It was found that all three polypeptides, after in vivo and in vitro treatment of the responder cell population, could enhance the allogeneic MLR. These polypeptides were also able to induce significant syngeneic MLR in systems where responder cells were used against irradiated syngeneic splenocytes. In addition, while beta 4 was shown to have a weak stimulatory effect on allogeneic MLR utilizing thymocytes as the responder cell type, alpha 1 could strongly induce such responses when syngeneic splenocytes were included into the culture system. Preincubation of purified mature T cells or thymocytes with alpha 1 has shown these cells to be the target of this polypeptide action. Thus, it appears that thymosin fraction 5 polypeptides not only initiate differentiation processes of immature T cells, but also exert their effects on mature T lymphocytes.